GRAMMATICAL ERROR ANALYSIS IN THESIS ABSTRACT: ENGLISH EDUCATION GRADUATE STUDENTS OF UIN SUSKA PEKANBARU - Hafni Hafsah (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Abstract An abstract is an entire picture of writing in terms of the information it contained. In terms of using English for the abstract is due to the reason that the language itself known internationally, thus makes it being recognized and read by lots of people. However, writing in English has never been easy for some people- particularly for English language students- who are demanding to write perfectly in terms of grammar. It is even more complicated due to fulfilling all the formalities; composing, developing logical ideas for the reader to comprehend its content. In this study, the writer aims to find out the errors in grammar in the thesis abstract of the graduate students of English Concentration of Post Graduate Program of State Islamic University of Sultan Syarif Qasim II (UIN SUSKA) Riau. This research uses a qualitative approach with a descriptive analysis technique. Samples of this research were collected purposively from the Post Graduate Program Library of the University in 2018, and the number is 17 (seventeen) abstracts from 2015 to 2017. The result of the data analysis shows that the types of error produced in a row are punctuation at the first place by 76.47% and then singular-plural by 47.06%, preposition and subject-verb agreement each by 29.41%, verb form and conciseness (long words) by 23.53%, and the last is Capitalizing by 5.88%. In addition, the omission of the article, especially article 'the', also occurred many times in the writing. Keywords: Error Analysis, Grammatical, Thesis Abstract, Writing